ANALISIS METODE MENGAJAR GURU PENDIDIKAN AGAMA KRISTEN BAGI ANAK MASA PRA-REMAJA TERHADAP PERKEMBANGAN FISIK DAN MENTAL - Anwar Three Millenium Waruwu; Orianto Hura (Edukasi : Jurnal Pendidikan Agama Kristen, 2022)
The pre-adolescent period is known as the teenage years and is usually referred to as the beginning of puberty. Many problems occur at this age, both in physical and mental development. One is that children are rebellious, challenging to manage, have no self-confidence, feel embarrassed about their appearance, get bored quickly, and so on. Of course, this is an obstacle for predominantly Christian religious education teachers in teaching students at this age. The purpose of writing this article is to analyze appropriate teaching methods to be applied by Christian Religious Education teachers for students at the pre-adolescent level. The method used is descriptive qualitative to provide an overview and answers to existing problems. The research results show that a teacher must teach by (i) conditioning the child's psychological needs, (ii) mentoring and disciplining children, (iii) providing a living example, and (iv) being a good motivator and listener for children.